2002
DOI: 10.2307/3345820
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between Perceptions of Conducting Effectiveness and Ensemble Performance

Abstract: This manuscript has been reproduced from the microfilm master. UMI films the text directly from the original or copy submitted. Thus, some thesis and dissertation copies are in typewriter face, while others may be from any type of computer printer.The quality of this reproduction is dependent upon the quality of the copy submitted. Broken or indistinct print colored or poor quality illustratnns and photographs, print bleedthrough, substandard margins, arxl improper alignment can adversely affect reproduction.I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
40
1
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 97 publications
4
40
1
1
Order By: Relevance
“…Performance evaluations in all these studies were carried out by individuals who listened to audio recordings and did not see the conductors. In a case where the conductor was seen, Van Weelden (2002) found moderate relationships between perceptions of conductor effectiveness and several variables, including facial expressions, and ensemble performances.…”
mentioning
confidence: 89%
“…Performance evaluations in all these studies were carried out by individuals who listened to audio recordings and did not see the conductors. In a case where the conductor was seen, Van Weelden (2002) found moderate relationships between perceptions of conductor effectiveness and several variables, including facial expressions, and ensemble performances.…”
mentioning
confidence: 89%
“…For example, African American conductors were perceived as superior for directing gospel music and less skilled for directing Western art song. 14,15 There may be a similar relationship between what conductors or audiences see in a choral arrangement and perceive in the choral sound, regardless of the sound produced by the chorus. This leads to two possibilities for future exploration, one perceptual and one acoustic.…”
Section: Discussionmentioning
confidence: 95%
“…Van Weelden 12,14 found that using conductors of different sex and race changed the perception of the choral sound, even when the listeners heard the same chorus recording for every conductor condition. She found that listeners had different expectations for conducting skills based on the race and the sex of the conductor.…”
Section: Discussionmentioning
confidence: 98%
“…Body movement serves for conveyance of emotion (e.g., Dahl & Friberg, 2007;Krahé, Hahn, & Whitney, in press) or the manner of expression (e.g., Davidson, 1993;Ohgushi, 2005: Vines, Krumhansl, Wanderley, Dalca, & Levitin, 2011. The posture of conductors affects performance ratings (Van Weelden, 2002). Facial expression plays a role in the decoding of performers' expressions (Ohgushi & Hattori, 1996;Thompson & Russo, 2007;Wöllner, 2008).…”
Section: Cues For Performers' Conveyance Of Intention or Audiences' Umentioning
confidence: 99%